IMPLEMENTATION OF ZAKAT ACCOUNTING BASED ON PSAK 109 IN LAZISMU PAYAKUMBUH CITY - Nopiardo, Widi (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2021)
The problem in this research is that not all components of the accounting report made by the officer, such as the report on changes in assets, are not yet available. The recording process still has a very simple report format according to the knowledge of the registrar. Reports on changes in funds are only recorded for the amount of money in and out without any other supporting information. The audit of zakat accounting reports is only carried out internally. From the initial data, the researchers are interested in discussing it. The method in this study uses a descriptive approach that aims to explain the solution to existing problems based on data to be analyzed and interpreted. The results showed that the application of Zakat Accounting based on PSAK 109 in LAZIS MU Payakumbuh City as follows: Initial Recognition of Zakat, the receipt of zakat is recognized when cash or other assets are received. Measurement After Initial Recognition, if there is a decrease in the value of non-cash zakat assets, the amount of loss incurred must be treated as a deduction of zakat funds or as a deduction for amil funds. Initial recognition of infaq / alms, infaq / alms received is recognized as bound or unrestricted infaq / alms funds in accordance with the objective of the donors of infaq / alms in the amount received. Measurement after initial recognition, donations / alms received can be in the form of cash or non-cash assets. Non-cash assets can be in the form of current or non-current assets. The distribution of infaq / alms, the distribution of infaq / alms funds is recognized as a deduction for infaq / alms funds in the amount given. Non-halal Funds, Non-halal receipts are all receipts from activities that are not in accordance with sharia principles, including receiving current accounts or interest from conventional banks. Presentation, Amil presents zakat funds, infaq / alms funds, amil funds, and non-halal funds separately in the balance sheet of the financial position statement. Amil zakat discloses matters related to zakat transactions. Transitional provisions, this statement applies to transactions of zakat and infaq / alms that occur on or after the effective date. Effective Date, the presentation of financial statements based on PSAK 109 began to apply LAZIS MU Payakumbuh City since 2015. Constraints so far in LAZIS MU Payakumbuh City are still limited human resources in applying PSAK 109. There is no PSAK 109 training program for managers who manage finances, so far it is still understand independently, so that the management's knowledge is limited. In addition, operational costs are also limited, so they have limitations in carrying out activities that are to improve the quality of human resources, especially in the financial sector.